Inklusionsorientierte Schulentwicklung Interdisziplinäre Rückblicke, Einblicke und Ausblicke - Frohn, Julia; Bengel, Angelika; Piezunka, Anne; Simon, Toni; Dietze, Torsten (Verlag Julius Klinkhardt, 2023)
The volume opens up an interdisciplinary approach to the topic of inclusion-oriented school development by examining and linking the dimensions of organizational, personnel and instructional development from the perspective of various (sub)disciplines and approaches. In addition to historically oriented inclusion research, which addresses questions of possible points of connection, path dependencies, or caesuras, the contributions to the volume are also devoted to analyzing the status quo of school inclusion, e.g., with regard to relevant characteristics of inclusion-oriented teaching or possible limits of inclusion research and implementation. In addition, future perspectives are derived from current scientific discourses and findings.